Influence of Mixing and Detention Time in Electro Coagulation Process to Treat Raw Water at Badak Singa Water Treatment Plant - Hary Pradiko; Evi Afiatun; Evan Fabian (Universitas Trisakti, 2018)
Source of raw water used at Badak Singa Water Treatment Plant come from surface water such as Cisangkuy River. This source of raw water is affected by conditions in the upstream, pollution along the stream, climate and weather. In the drinking water supply system, turbidity is one important factor for several reasons such as aesthetic factor, burden to filtration, and interfere the disinfection process. Electro coagulation is one of water treatment method that combines the process of coagulation, flotation, and electrochemical. Aims: This research aims to see at the ability of the electro coagulation process in reducing turbidity as an alternative to substitute the conventional coagulation system. Methodology and results: This research carried out by testing electro coagulation with variations in mixing, current density produced by voltage 10, 20 and 30 volt and detention time 5, 10, 20 and 30 minute to reduce the initial turbidity of 100 NTU. The result are that: the efficiency of electro coagulation with mixing is better than electro coagulation without mixing to reduce the initial turbidity of 100 NTU; the final turbidity value of the processing result is better as the length of detention time used and meet the quality standard from detention time of 10 minute; the higher the current density given and the longer the detention time used, the higher the processing efficiency and the formed flock volume is deposited. Conclusion, significance and impact study: A good turbidizing removal process using electrocoagulation requires the agitation process and long detention time.